SARS-CoV-2 Infection Boosts MX1 Antiviral Effector in COVID-19 Patients - Juan Bizzotto; Pablo Sanchis; Mercedes Abbate; Sofía Lage-Vickers; Rosario Lavignolle; Ayelén Toro; Santiago Olszevicki; Agustina Sabater; Florencia Cascardo; Elba Vazquez; Javier Cotignola; Geraldine Gueron (iScience, 2020)
Summary: In a published case-control study (GSE152075) from SARS-CoV-2-positive (n = 403) and -negative patients (n = 50), we analyzed the response to infection assessing gene expression of host cell receptors and antiviral proteins. The expression analysis associated with reported risk factors for COVID-19 was also assessed. SARS-CoV-2 cases had higher ACE2, but lower TMPRSS2, BSG/CD147, and CTSB expression compared with negative cases. COVID-19 patients' age negatively affected ACE2 expression. MX1 and MX2 were higher in COVID-19 patients. A negative trend for MX1 and MX2 was observed as patients' age increased. Principal-component analysis determined that ACE2, MX1, MX2, and BSG/CD147 expression was able to cluster non-COVID-19 and COVID-19 individuals. Multivariable regression showed that MX1 expression significantly increased for each unit of viral load increment. Altogether, these findings support differences in ACE2, MX1, MX2, and BSG/CD147 expression between COVID-19 and non-COVID-19 patients and point out to MX1 as a critical responder in SARS-CoV-2 infection.